Les zones agricoles protégées (ZAP) : valoriser l’identité agricole locale - Gisèle Vianey (Projets de Paysage)
In order to meet the ongoing needs of the urban spread out, land consumption continues. Regulatory tools of the increasing land consumption, morre partcularly agricultural ones, are at the disposal of local collectives in the implementation of planning documents. However, these tools that are supposed to be a mean of dialogue between land planning policies and agricultural policies are not often used. When implemented by collectivities, these tools help to maintain an elitist agricultural activity and to produce an emblematic landscape. These tools do not help in holding the urban spread nor to recognize the hybrid specificity of the peri-urban area.